2023
DOI: 10.1186/s12871-023-02019-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect and safety of dexmedetomidine as an adjuvant to local anesthetics in erector spinae plane block: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Dexmedetomidine (DEX) has been thought to be an effective adjuvant to local anesthetics (LAs) in erector spinae plane block (ESPB), however, this method of use is not recorded in the drug instructions. Hence, our meta-analysis will evaluate its efficacy and safety for the first time. Methods A systematic search of published articles was conducted in the PubMed, Embase, Web of science, and Cochrane Library databases up to July 17, 2022, u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Comparable sleep alterations have not been documented with dexmedetomidine administration (Figure). 6,7 A recent meta-analysis of 5 randomized controlled trials (381 adults total) compared the sleep quality of patients who received dexmedetomidine pre-, peri-, or postoperatively to either placebo or other analgesics or sedating medications after elective surgery. Significant sleep quality improvements were observed in sleep efficiency (ratio of total sleep time/ time observed) and arousal (arousals per hours of sleep) indices, as well as decreased "light" (stage 1) and increased "deeper" (stage 2) sleep among those who received dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparable sleep alterations have not been documented with dexmedetomidine administration (Figure). 6,7 A recent meta-analysis of 5 randomized controlled trials (381 adults total) compared the sleep quality of patients who received dexmedetomidine pre-, peri-, or postoperatively to either placebo or other analgesics or sedating medications after elective surgery. Significant sleep quality improvements were observed in sleep efficiency (ratio of total sleep time/ time observed) and arousal (arousals per hours of sleep) indices, as well as decreased "light" (stage 1) and increased "deeper" (stage 2) sleep among those who received dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed no differences with respect to stage 3 or REM sleep. 6 A randomized, double-blind, placebo-controlled study by Wu et al 7 examined intraoperative dexmedetomidine infusion versus saline for 96 adults undergoing endoscopic sinus surgery. Each patient was observed for 1 night both preoperatively and postoperatively, where sleep architecture independent of sedating medications was analyzed using polysomnography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations